Exosomes isolated during dopaminergic neuron differentiation suppressed neuronal inflammation in a rodent model of Parkinson's disease. (6th February 2022) - Li, Yongang; Li, Zongshan; Gu, Jiachen; Xu, Xiaomin; Chen, Huimin; Gui, Yaxing
Highlights: Exosomes isolated during dopaminergic neuron differentiation suppressed neuronal inflammation in a rodent model of Parkinson's disease. Injection of BMSC induced-Exosomes into the striatum rescued the rotation behavior and climbing speed in the PD rats. Wnt5a was found to be enriched in BMSC induced Exosomes, which could be effectively transferred to the substantia nigra of PD rats. Abstract: Our previous investigation showed Wnt signal pathway was significantly activated during DA neuron differentiation of epiblast-derived stem cells. In this study, we next attempt to examine the therapeutic potential of the purified exosomes derived bone marrow mesenchymal stem cells (BMSCs) by administrating exosomes into the rat striatum of parkinson's disease (PD) animal model. Results revealed that the protein levels of interleukin (IL)-6, IL-1β, tumor necrosis factor-alpha (TNF-α), and reactive oxygen species (ROS) in the substantia nigra of PD rats were down regulated after injection of BMSC induced-Exosomes into the striatum of PD model compared to BMSC quiescent-Exosomes. In addition, the expression of ionized calcium binding adaptor molecule 1 (Iba1) mRNA was significantly decreased, while the expression of tyrosine hydroxylase (TH) mRNA was increased after injection of BMSC induced-Exosomes. Injection of BMSC induced-Exosomes into the striatum rescued the rotation behavior and climbing speed in the PD rats. More importantly, Wnt5a was found to be enriched in BMSC induced Exosomes, which could be effectively transferred to the substantia nigra of PD rats. In conclusion, these findings demonstrated that exosomes isolated during dopaminergic neuron differentiation could rescue the pathogenic features of Parkinson's disease by reshaping the inflammatory microenvironment in the substantia nigra and repairing the injury to DA nerves.